Evaluation of MODIS and Himawari‐8 Low Clouds Retrievals Over the Southern Ocean With In Situ Measurements From the SOCRATES Campaign. Issue 3 (15th March 2021) - Kang, Litai; Marchand, Roger; Smith, William
Abstract: Aircraft observations collected during the Southern Ocean Cloud Radiation Aerosol Transport Experimental Study in January‐February of 2018 are used to evaluate cloud properties from three satellite‐imager datasets: (1) the Moderate Resolution Imaging Spectroradiometer level 2 (collection 6.1) cloud product, (2) the CERES‐MODIS Edition 4 cloud product, and (3) the NASA SatCORPS Himawari‐8 cloud product. Overall the satellite retrievals compare well with the in situ observations, with little bias and modest to good correlation coefficients when considering all aircraft profiles for which there are coincident MODIS observations. The Himawari‐8 product does, however, show a statistically significant mean bias of about 1.2 μm for effective radius ( r e ) and 2.6 for optical depth ( τ ) when applied to a larger set of profiles with coincident Himawari‐8 observations. The low overall mean‐bias in the r e retrievals is due in part to compensating errors between cases that are non‐ or lightly precipitating, with cases that have heavier precipitation. r e is slightly biased high (by about 0.5–1.0 μm) for non‐ and lightly precipitating cases and biased low by about 3–4 μm for heavily precipitating cases when precipitation exits near cloud top. The bias in non‐ and lightly precipitating conditions is due to (at least in part) having assumed a drop size distribution in the retrieval that is too broad. These biases in the r e ultimately propagate into the retrieved liquid water path and number concentration. Plain Language Summary: Clouds play a crucial role in the weather and climate system. Satellite data can provide useful information on cloud properties (such as the size of the cloud droplets, the amount of the liquid water, and the number of droplets in a given volume of the clouds) over large areas and at high spatial and temporal resolutions. However, satellite cloud properties are determined or retrieved from satellite measurements by employing a variety of simplifying assumptions that can lead to large uncertainties in some conditions. In situ measurements of clouds from aircraft provide more direct observations and can be used as ground truth to evaluate and improve the performance of the satellite retrievals. This study focuses on clouds over the Southern Ocean (SO) and uses aircraft measurements from Southern Ocean Cloud Radiation Aerosol Transport Experimental Study (SOCRATES) in January‐February of 2018 to evaluate cloud properties from three satellite observations. It is found that the satellite observations generally compare well with aircraft measurements with little bias. However, satellite observations tend to overestimate the size of the cloud droplets, when clouds are not precipitating or are lightly precipitating, while for clouds with heavier precipitation, the satellite observations tend to underestimate the size of the cloud droplets. Key Points: Overall imager‐based bi‐spectral retrievals are found to work reasonably well for Southern Ocean overcast (closed‐cell) stratocumulus Effective radius is biased high by 0.5–1.0 μm for non or lightly‐precipitating cases and biased low by about 3–4 μm otherwise These biases are due in part to (1) the assumed drop size distribution being too broad, and (2) precipitation being present near cloud top